2014
DOI: 10.5306/wjco.v5.i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of research on the effects of exercise training in breast cancer survivors: A systematic review of the literature

Abstract: Exercise training appears to be safe for most breast cancer patients and improvements in physiological, psychological, and functional parameters can be attained with regular participation in moderate intensity exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
110
0
32

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 49 publications
9
110
0
32
Order By: Relevance
“…Of 36 studies identified, only 10 implemented strength training. These data are consistent with what was found in the review of intervention programs including physical exercise in patients with breast cancer, conducted in 2010 by the ACSM, in which only 11 of 53 studies included work force 24 ; a systematic review by Bataglini et al 21 in 2014 identified 11 studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Of 36 studies identified, only 10 implemented strength training. These data are consistent with what was found in the review of intervention programs including physical exercise in patients with breast cancer, conducted in 2010 by the ACSM, in which only 11 of 53 studies included work force 24 ; a systematic review by Bataglini et al 21 in 2014 identified 11 studies.…”
Section: Discussionsupporting
confidence: 86%
“…8,21 In our aerobic training program, which utilized an intense split method, the same phenomenon was evident but with an average increase in oxygen consumption of 5.1 ml kg −1 min −1 , equivalent to 20%. This higher value of increased oxygen consumption obtained in our study relative to the values observed in studies involving other groups might have resulted from our use of a higher-intensity exercise, which is consistent with existing evidence that this type of exercise leads to more elevated levels of peak oxygen consumption.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As for the safety of breast cancer patients practicing physical exercises, one meta-analysis of 51 studies performed in the last 25 years proves that low and moderate intensity physical exercise is safe and beneficial (24).…”
Section: Introductionmentioning
confidence: 99%
“…In United States, only 1 in 5 adult American (21%) meet the 2008 Physical Activity Guidelines and less than 3 in 10 high school students get at least 60 minutes of moderate to high intensity physical activity every day. 2 Supervised exercise performance has shown remarkable effectiveness, but is associated with poor compliance the long-term, 3 therefore it becomes necessary to include physical activity as an integral part of everyday lifestyle. To change the routine of the life in terms of implementing the physical activity, it is necessary to create a model that allows longterm therapeutic efficacy.…”
mentioning
confidence: 99%